Examining Polytechnic Students’ Metacognitive Reading Strategies Using Think-Aloud Protocols Analysis - Deri, Mornita; Shamsudin, Sarimah (International Journal of Engineering and Technology, 2018)
Text comprehension is the essence of reading. It plays a vital role in learning especially in the acquisition, sharing, and construction of knowledge. Many researchers have highlighted that metacognitive strategies are critically important aspects of skilled reading. Metacognition is basically referred to thinking about thinking. In the field of reading, metacognitive reading strategies are those activities that make readers aware of their thinking as they engage in reading tasks. Since reading is a cognitive enterprise, readers must apply metacognitive knowledge and must invoke conscious and deliberate strategies in order to achieve comprehension of text successfully. In this study, we will present the findings of the research which concentrate on metacognitive reading strategies used by students of Politeknik Kuching Sarawak when reading English texts. From the think aloud analysis, it was revealed that comprehension problems are the result of the studentsâ€™ limited strategy repertoires and poor strategy choice and comprehension monitoring. From the results of the study, we concluded that teaching metacognitive reading strategies should be taken into account in developing studentsâ€™ reading comprehension.Â Â